The influence of two type’s aerobic exercise in two different conditions on the thermal resistance of the airways resistance and bronchospasm athlete male students in Ahwaz City - Mahmood Asle Mohammadizadeh (Iranian South Medical Journal, 2014)
Abstract Background: Respiratory system is the only body system that is directly exposed to environmental temperature and humidity can cause different reactions. Respiratory rate at rest and exercise in adolescents also because the depth is less than most adults. This requires that the increase in respiratory complications in these patients should be examined. The aim of this study the resistance of the airways and the status of bronchospasm in two different conditions of hot and cold air in young male athletes. Material and Methods: Thirty-five high school students volunteer in Ahwaz city (16-18) year’s average height (178 cm), weight (66 kg), body mass index of 25/14. 92 percent of lung function of FVC, The winter air temperature 14 ° C and 68% relative humidity and air temperature in spring, 42 ° C and relative humidity was 76%. Before running the tests measurements are recorded. Low intensity aerobic exercise protocols used to measure the bulk has been. High-intensity aerobic exercise test to measure the Astrand on the treadmill in the winter (January) and spring (June) has been made. In the seasons before and after the exercise test, pulmonary parameters of FVC, FEV1, FEV1/FVC were measured. Using t-test, paired and independent results after the test with a (p ≤ 0.05) in two different storage temperatures and at high intensity and low-practice cases are compared. Results: Results showed that compared FEV1, FEV1/FVC to the pre-test parameters and test the bulk test in winter and spring and winter and spring Strand test is significant. Astrand test results as well as between the Bulks test in the winter and spring, significant differences were observed. According to the results, only 4 people (14%) followed by the low-intensity activity in spring and develop bronchospasm were airway resistances. On the other hand, high intensity activities in winter in 14 patients or 40% of subjects are bronchospasm and increased resistance of the air way. Conclusion: General exercise with high intensity in cold weather conditions caused evoked of the lungs airway and and restricted the airflow (than exercise with low intensity in warm weather conditions) in boy's students.